Propaganda and Preservation: Missed Opportunities and Inadvertent Archives in Radio Research. Issue 1 (2nd January 2019) - Jenemann, David
Abstract : Radio research of the 1930s and 40s poses a challenge to the contemporary scholar of broadcast history. In the early days of radio research, scholars and practitioners often placed emphasis on material extraneous to the broadcast content rather the content itself. As a result, radio scripts and broadcast material that might have been preserved for contemporary scholarship was at best inconsistently and imperfectly preserved, and at worst discarded altogether. Considering the development of radio research in the 1930s and 40s, Leo Löwenthal and other members of the Frankfurt School often found that their emphasis on content analysis meant they were at the center of methodological disputes that put them at odds with their peers but firmly on the side of today's radio historians and preservationists. In this essay, I argue that the historical emphasis on radio audiences and effects analysis that tends to predominate early radio research often obscured the broadcast content that produced those effects. However, with their studies of the techniques of right-wing radio agitators, the Frankfurt School's insistence on content analysis inadvertently helped preserve historically significant broadcast material that not only would have otherwise been lost, but which also provides an important template for understanding contemporary manifestations of demagoguery. For today's scholars invested in the preservation of broadcast content, following the trail left by these methodological iconoclasts can help us fill in missing pieces of radio's historical puzzle.